2022
DOI: 10.1002/cjoc.202200355
|View full text |Cite
|
Sign up to set email alerts
|

Tuning Acceptor Length in Photocatalytic Donor‐Acceptor Conjugated Polymers for Efficient Solar‐to‐Hydrogen Energy Conversion

Abstract: gradually changing from yellow-green of PDBTSO to red of P(BDT-DBTSO) with the increment of BDT content (Figure 1a), and insoluble in most common organic solvents and water. Their structures were characterized by elemental analysis, solid-state 13 C NMR ( 13

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 80 publications
0
11
0
Order By: Relevance
“…According to Li et al . report on the synthesis of D‐A benzodithiophene (BDT)‐based copolymer (P(BDT‐DBTSO 79 ), when visible light was used to illuminate the dispersion solution of (P(BDT‐DBTSO 79 ) in DMF/triethylamine/H 2 O in the presence of Pt (3 wt %), HER value was 119.3 mmol g −1 h −1 [93] . Jiang et al .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Li et al . report on the synthesis of D‐A benzodithiophene (BDT)‐based copolymer (P(BDT‐DBTSO 79 ), when visible light was used to illuminate the dispersion solution of (P(BDT‐DBTSO 79 ) in DMF/triethylamine/H 2 O in the presence of Pt (3 wt %), HER value was 119.3 mmol g −1 h −1 [93] . Jiang et al .…”
Section: Resultsmentioning
confidence: 99%
“…[88] According to Li et al report on the synthesis of D-A benzodithiophene (BDT)-based copolymer (P(BDT-DBTSO 79 ), when visible light was used to illuminate the dispersion solution of (P(BDT-DBTSO 79 ) in DMF/triethylamine/ H 2 O in the presence of Pt (3 wt %), HER value was 119.3 mmol g À 1 h À 1 . [93] Jiang et al prepared the random copolymer PyBS-3 with a monomer feed ratio of 25 : 75 that shows a high HER of 1.05 mmol h À 1 under UV/Vis light irradiation using AA as the hole-scavenger and an external quantum efficiency of 29.3 % at 420 nm. [92] Also, the optimum CTF-0.5BT sample produced by doping of CTF-based photocatalysts with benzothiadiazole (BT) achieved a photocatalytic activity for solar hydrogen production up to 2.24 mmol h À 1 .…”
Section: Photocatalytic Hydrogen Evolutionmentioning
confidence: 99%
“…Compared with the Yamamoto homocoupling products PCZN‐1 and PCZN‐6, the Yamamoto cross‐coupling ones from PCZN‐2 to PCZN‐5 displayed a higher HER activities, which is mainly ascribed to the donor–acceptor structures promoting charge transfer and separation. [ 43 ] The steady‐state photoluminescence spectroscopy revealed that PCZN‐4 has the lowest emission intensity when compared with that of the PCZN‐1 and PCZN‐6, endowing it with the lowest charge recombination rate (Figure 5c). The photogenerated electrons and holes are inclined to effectively separate due to the existence of donor and acceptor moieties in PCZNs samples.…”
Section: Resultsmentioning
confidence: 99%
“…Blocking layer: A selective barrier layer constructed on the catalyst surface has been shown to inhibit unnecessary chlorination on the anode, so a similar method can be used to protect the cathode to improve the durability of the catalyst. [ 58‐63 ] Recent examples related to cathodic protection have been demonstrated. It has been reported that a Cr(OH) 3 selective blocking layer on Pt cathode can effectively inhibit the competitive hypochlorite reduction in the chlorate process, thus improving HER selectivity.…”
Section: Designing Of Oer and Her Catalysts For Direct Seawater Split...mentioning
confidence: 99%